If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -42 = 6(y + 12) Reorder the terms: -42 = 6(12 + y) -42 = (12 * 6 + y * 6) -42 = (72 + 6y) Solving -42 = 72 + 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. -42 + -6y = 72 + 6y + -6y Combine like terms: 6y + -6y = 0 -42 + -6y = 72 + 0 -42 + -6y = 72 Add '42' to each side of the equation. -42 + 42 + -6y = 72 + 42 Combine like terms: -42 + 42 = 0 0 + -6y = 72 + 42 -6y = 72 + 42 Combine like terms: 72 + 42 = 114 -6y = 114 Divide each side by '-6'. y = -19 Simplifying y = -19
| 42=3*5+b | | 17=9+4a | | 7x+4=-x-84 | | 7x-9=47-7x | | x-7=-13+13x | | x+2=x-1/4 | | 10(g-5)=-80 | | 175000.00+550.00x=300440.00 | | x+3x=50 | | x+8+x=16 | | -9=-3x+x+3 | | ((32x^3)-(28x^2)-47x-12)=0 | | (-5/2x)+(3/4x)=(-3/4) | | 2(-1-1x)=-26 | | ((32x^3)-(28x^2)-47x-12)/(8x+3) | | 2x+7=4x+65/9 | | 7x+1=-3x-19 | | -2x+2-x=32 | | 4x+2-x=29 | | 8x-2(x+5)-7+5x=-21+4+x | | 10+4x-x=64/7 | | 8x-2(x-5)-7+5x=21+3x | | -3+4x-7x=21 | | 118=4(20)+38 | | 8d-3/5=5d+3/2 | | 51=2x+7x+6 | | p=23/3(18) | | 106/5=7x+4x-4/5 | | p=7(18) | | 10x+7=20x | | p=6(18) | | 6a-4a-5=7a-23 |